Local Agglomeration, Entrepreneurship and the Great Recession: Evidence from Italian Industrial Districts - Giorgio Brunello; Monica Langella (Institute for the Study of Labor (IZA), 2014)
We ask whether local agglomeration affects how recessions impact on entrepreneurship by comparing the probability of being an entrepreneur before and after the Great 2008 Recession in local labour markets where industrial districts are present and in comparable areas. Using Italian Labour Force quarterly data from 2006 to 2011 and a "difference-in-differences" approach, we find that for males aged 40 to 55, who are more likely to be entrepreneurs, the negative effect of the recession on entrepreneurship has been sharper in areas with industrial districts. After examining alternative explanations ranging from specialization to access to credit, from propensity to export to the industrial sector we conclude that our findings are consistent with the view that intense social interaction in industrial districts acts as a multiplier that amplifies the response to shocks.
Keywords: J21; J24; 330; entrepreneurship; recession; Italy; industrial districts